2016
DOI: 10.1364/boe.7.002269
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of optical properties of basal cell carcinoma and differentiation of BCC subtypes by high-definition optical coherence tomography

Abstract: High-definition optical coherence tomography (HD-OCT) features of basal cell carcinoma (BCC) have recently been defined. We assessed in vivo optical properties (IV-OP) of BCC, by HD-OCT. Moreover their critical values for BCC subtype differentiation were determined. The technique of semi-log plot whereby an exponential function becomes linear has been implemented on HD-OCT signals. The relative attenuation factor (µraf ) at different skin layers could be assessed.. IV-OP of superficial BCC with high diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…When used individually and independently, both OCT and RCM can noninvasively detect superficial and nodular BCCs with sensitivities and specificities in the range 80% to 95% and 70% to 90%, respectively [12][13][14]. Furthermore, other studies have reported the ability of OCT to reliably detect the depth of BCCs in vivo [15][16][17][18][19][20].…”
Section: Editorialmentioning
confidence: 99%
“…When used individually and independently, both OCT and RCM can noninvasively detect superficial and nodular BCCs with sensitivities and specificities in the range 80% to 95% and 70% to 90%, respectively [12][13][14]. Furthermore, other studies have reported the ability of OCT to reliably detect the depth of BCCs in vivo [15][16][17][18][19][20].…”
Section: Editorialmentioning
confidence: 99%
“…We investigated the use of a non-invasive optical imaging method, based on integrating reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) into a single instrument. Many studies have shown that both OCT and RCM imaging, when used individually and independently can noninvasively detect superficial and nodular BCCs with sensitivities and specificities in the range 80-95% and 70-90%, respectively [20][21][22][23][24][25][26]. Since RCM provides cellular-level resolution, it can be used to accurately detect the morphological features of BCCs and provide high diagnostic accuracy.…”
Section: Ivyspringmentioning
confidence: 99%
“…57 A study in HD-OCT demonstrated that subdifferentiation of BCC can be made with a higher accuracy when applying optical properties compared to morphology analysis alone. 58 The monitoring of therapeutic response to treatment is another field of OCT research that has developed recently. A higher accuracy of identifying residual BCC lesions and confirmation of complete response after photodynamic therapy compared to clinical evaluation has been shown in Ref.…”
Section: Nonmelanoma Skin Cancermentioning
confidence: 99%